Multiple Exposures Enhance Both Item Memory and Contextual Memory Over Time - Chen, Haoyu; Yang, Jiongjiong (Frontiers in Psychology, 2020)
Repetition learning is an efficient way to enhance memory performance in our daily lives and educational practice. However, it is unclear to what extent repetition or multiple exposures modulates different types of memory over time. The inconsistent findings on it may be associated with encoding strategy. In this study, participants were presented with pairs of pictures (same, similar, different) once (Experiment 1) or three times (Experiment 2) and were asked to make a same/similar/different judgment. By this an elaborative encoding is more required for the ‘same’ and ‘similar’ conditions than the ‘different’ condition. Then after intervals of 10-min, 1-day and 1-week, they were asked to perform a recognition test to discriminate a repeated and a similar picture, followed by a remember/know/guess assessment and a contextual judgment. The results showed that after learning the objects three times, both item memory and contextual memory improved. Multiple exposures enhanced the hit rate for the ‘same’ and ‘similar’ conditions, but did not change the false alarm rate significantly. The recollection, rather than the familiarity, contributed to the repetition effect. In addition, the memory enhancement was manifested in each encoding condition and retention interval, especially for the ‘same’ condition and at 10-min and 1-day intervals. These results clarify how repetition influences item and contextual memories during discriminative learning, and suggest that multiple exposures render the details more vividly remembered and retained over time when elaborative encoding is emphasized.